Ответ:
или
Пошаговое объяснение:
+
Воспользуемся правилом:
Сделаем замену и
Причем т.к.
Получаем:
=
= =
Обратная замена:
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
или
Пошаговое объяснение:
Воспользуемся правилом:
Сделаем замену
и ![y=cos\alpha y=cos\alpha](https://tex.z-dn.net/?f=y%3Dcos%5Calpha)
Причем
т.к. ![sin^{2}+cos^{2}=1 sin^{2}+cos^{2}=1](https://tex.z-dn.net/?f=sin%5E%7B2%7D%2Bcos%5E%7B2%7D%3D1)
Получаем:
=
=
=
=
=
=
=
=
=
=
=![\frac{y}{x}- \frac{x}{y} +1 \frac{y}{x}- \frac{x}{y} +1](https://tex.z-dn.net/?f=%5Cfrac%7By%7D%7Bx%7D-%20%5Cfrac%7Bx%7D%7By%7D%20%2B1)
Обратная замена: